Strategi Kebijakan Lingkungan Program Citarum Harum Di Kabupaten Bandung - Yayan Andri; Yaya Mulyana Abdul Aziz (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
So great is the loss suffered due to the contamination of the Citarum River for decades. Starting from the damage in the Citarum Hulu watershed (DAS) to the pollution of industrial waste and domestic waste. Not to mention, flood disasters due to overflowing rivers and sedimentation that often occur in the Bandung Basin, especially Baleendah and Dayeuhkolot. The research method used in this study is descriptive analysis with the type of research being qualitative. The qualitative approach was chosen with the consideration that this method is expected to obtain real data and be able to examine research problems in depth so that the expected results can be obtained.  The use of this qualitative research approach is felt to be very appropriate in the study of public administration. The results of the research is an appropriate step in controlling the damage and pollution of watersheds. One form of government policy strategy by issuing Presidential Decree no. 15 of 2018 concerning the Acceleration of Pollution Control and Damage to the Citarum River Basin.  With the existence of the Citarum Harum Program policy, it is an environmental policy strategy by observing, controlling problematic environmental conditions and even having to immediately restore the image of the Citarum River which was once tarnished in the eyes of the world as the dirtiest river in the world. With a collaborative step that is able to cover the Siliwangi Kodam III Sector which is divided into 22 Task Forces along the banks of the Citarum River, this is a strategy in restoring the problems that occur in the Citarum River. This policy program will end in 2025, so there must be a follow-up to the next program as well as a success evaluation program so that it does not repeat itself like the previous policy programs which were considered less successful and cost a large amount.